Effectiveness and distributional impacts of payments for reduced carbon emissions from deforestation - Knoke, Thomas M.; Weber, Michael; Barkmann, Jan; Pohl, Perdita; Calvas, Baltazar; Medina, Carolina; Aguirre, Nikolay; Günter, Sven; Stimm, Bernd; Mosandl, Reinhard; von Walter, Frank; Maza, Byron; et al. (ERDKUNDE, 2009)
This paper analyses the effectiveness and distributional effects of payments to avoid tropical deforestation. As a first aspect, we investigated whether or not expected payments for avoided deforestation would be acceptable for tropical farmers in Southern Ecuador, with the study area located directly adjacent to the Podocarpus National Park. Second, we explored possible distributional effects resulting from voluntary or mandatory remuneration schemes to avoid deforestation. Finally, a productive sustainable land use was conceptualised to be combined with payments for avoided deforestation to avoid leakage (i.e. deforestation processes elsewhere when avoided at a given farm). Farm level land use scenarios with (“business as usual”) and without deforestation (“conservation strategy”) were compared. Compensation per Mg Carbon (C) that is not emitted into the atmosphere under the “conservation strategy” was derived to achieve a monetary land net present value (NPV, sum of discounted future net revenues) equal to the NPV obtained under “business as usual”. Avoided carbon emissions were computed from above ground C in tropical forests of the project area and supplemented by information on soil carbon from another study. Economic data for cattle pasturing were obtained from a farm survey (130 households) to investigate distributional effects. To derive sustainable land use concepts, a risk sensitive bioeconomic farm model was used that considered effects of risk compensation when combining pasture with reforestation of abandoned farm lands and selective logging of natural forests. The results showed that only a few farmers (20 out of 130) would possibly accept a compensation price of US$ 10 per Mg avoided C emission, a C-compensation that is believed by other authors to reduce deforestation by 65%. Rather a compensation of around US$ 25 per Mg C was necessary to address compensation requirements of farmers who hold 50% of the tropical forest area in our study. The implementation of a voluntary remuneration scheme for avoided deforestation would not introduce systematic distributional effects (such as that only the biggest farmers would benefit from compensation), while a mandatory and enforced ban on deforestation coupled with a “fair” compensation payment equal to mean compensation requirements may lead to undesirable effects for many farmers. Finally, we demonstrate a mixed sustainable land use concept that depended on cheap credits for reforestation of abandoned pasture lands. This concept was able to stop farm level deforestation and to enlarge the economic value of farms through various combined land use options (agricultural and forestry options). The combination of land uses led to risk ..compensatory effects and a more efficient land use by reintegrating unproductive abandoned areas back into the economical process. In our conclusion a combination of payments for avoided deforestation along with productive land use concepts provided a viable solution for tropical forest conservation.